Communication Generates Behavioral Intentions to Visit Historical Tourism Objects - Diah Cori Kuswardani; Tri Endang Yani; Iswahyu Pranawukir; Vensy Vydia; Aprih Santoso (Universitas Dharma Wacana, 2022)
The purpose of this study is to contribute to building behavioral intentions through service quality and experience quality. Perceived Value is expected to play a role as a mediation in tourism objects in the city of Semarang. The population is all visitors to tourist attractions in the city of Semarang, while the sample is determined on the basis of Tables Isaac and Michael of 190, respondents are determined using the Proportionate Stratified Random Sampling technique. Path analysis is used as an analytical tool with the Sobel test to determine the results of mediation between exogenous and endogenous variables. The results of hypothesis testing show that behavior intention can be manifested by service quality and experience quality through perceived value as mediation. Perceived value can be implied through service quality and experience quality while Perceived Value directly significantly influences Behavior Intention. The results of the Sobel test calculation show a value of 2.114 meaning that the Service quality and Experience quality variables have a significant influence on Behavioral Intention through Perceived Value. The Adjusted R-Square value obtained is 0.868, meaning that behavioral intention can be explained by service quality, experience quality and perceived value of 86.8% and the remaining 13.2% is explained by other variables outside this study